ВОКАЛЬНА ПІДГОТОВКА МАЙБУТНЬОГО ВЧИТЕЛЯ МУЗИКИ ЗА ВИМОГАМИ КРЕДИТНО-МОДУЛЬНОЇ СИСТЕМИ (Педагогіка вищої та середньої школи, 2008)
The vocal training of the Future Music Teacher according to the demands of the Credit and Module System. The content of the educational program of the voice training for the students of musical-pedagogical department of arts faculty on the Credit and Module System is revealed in this article.